2019
DOI: 10.1016/j.ejmech.2019.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Anti-parasitic activity of polyether ionophores

Abstract: Despite some progress in recent years, the fight against parasitic diseases still remains a great challenge. Parasitic diseases affect primarily (but not exclusively) the poorest people living in underdeveloped regions of the world. The distribution of parasitoses are linked to tropical and subtropical climate conditions, to population growth and to impoverishment. If not treated, parasitic diseases may lead to serious health problems, and even death. Particularly vulnerable groups include infants and young ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 184 publications
(291 reference statements)
0
28
1
Order By: Relevance
“…Salinomycin is globally used as an agent to prevent coccidiosis in poultry production; however, it has a strong ability to modulate the birds' GIT microbial populations [15]. Its activity based on transporting ions (K + and Na + ) and disrupting the cell membrane ion gradient is mainly directed against Gram-positive microorganisms [16,17]. The combination of salinomycin and other compounds such as antimicrobials, bacteriocins, probiotics, prebiotics, butyrate, and comparisons of these materials have been repeatedly examined, primarily for the control of coccidiosis [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Salinomycin is globally used as an agent to prevent coccidiosis in poultry production; however, it has a strong ability to modulate the birds' GIT microbial populations [15]. Its activity based on transporting ions (K + and Na + ) and disrupting the cell membrane ion gradient is mainly directed against Gram-positive microorganisms [16,17]. The combination of salinomycin and other compounds such as antimicrobials, bacteriocins, probiotics, prebiotics, butyrate, and comparisons of these materials have been repeatedly examined, primarily for the control of coccidiosis [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Polyether ionophores have been used in veterinary medicine for decades as non-hormonal growth promoters and as agents to control coccidiosis [1][2]. In addition to the industrial use of ionophores in animal husbandry [3], some of them show anti-fungal, anti-viral, and anti-cancer activity [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging more recently as novel anticancer agents of natural origin are select polyether ionophores, such as salinomycin . Salinomycin ( SAL , 1 , Scheme ), isolated from Streptomyces albus , exhibits a broad spectrum of bioactivity . SAL is commercially used as a food additive and a growth promoter due to its potent coccidiostatic and antibacterial properties .…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Salinomycin (SAL, 1, Scheme 1), isolated from Streptomyces albus, [15] exhibits a broad spectrum of bioactivity. [16,17] SAL is commercially used as a food additive and a growth promoter due to its potent coccidiostatic and antibacterial properties. [18] More recently, SAL has been also found to exhibit potent antifungal, antiparasitic and antiviral activity, [16,17] and extensive screening studies by Gupta et al identified SAL as a very promising anticancer agent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation